2023
DOI: 10.1371/journal.pone.0287053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flanged diffuser divergence angle on wind turbine: A numerical investigation

Abstract: Power augmentation in a small-scale horizontal axis wind turbine, with its rotor encased in a flanged diffuser is explored. The power output of the wind turbine varies with changes in the diffuser design and the resulting back pressure. Reduction in this back pressure also results in early flow separation at the diffuser surface, which hinders turbine performance. The main aim of this study is to numerically investigate the local configuration of the wind turbine location inside the diffuser by varying diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…This research employs the CFD software ANSYS Fluent 2023 R2 to study the threedimensional flow and acoustic fields. In this study, the SST k-ω turbulence model is used as a closure for the Reynolds-averaged Navier-Stokes (RANS) equations, for this model accounts for turbulent shear stress transport, exhibits good performance in near-wall boundary layers [35], and is reliable in predicting flow separation under adverse pressure gradients [34]. Thus, it gains a broad consensus as to its suitability for wind turbine applications [23,[27][28][29][30][31][32][33]35].…”
Section: Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%
See 3 more Smart Citations
“…This research employs the CFD software ANSYS Fluent 2023 R2 to study the threedimensional flow and acoustic fields. In this study, the SST k-ω turbulence model is used as a closure for the Reynolds-averaged Navier-Stokes (RANS) equations, for this model accounts for turbulent shear stress transport, exhibits good performance in near-wall boundary layers [35], and is reliable in predicting flow separation under adverse pressure gradients [34]. Thus, it gains a broad consensus as to its suitability for wind turbine applications [23,[27][28][29][30][31][32][33]35].…”
Section: Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%
“…Consideration of the tip clearance in the design of a DAWT is recommended by researchers [32,39], who point out that it is related to the aerodynamic and acoustic characteristics of the DAWTs. Diffuser opening angle was taken as a design parameter in studies performed by researchers [19,30,32,34], who revealed its significant effects on DAWT performance. In the summary of the papers surveyed, some key parameters regarding DAWT design have been collected, such as diffuser flange height/angle, diffuser profile/length/opening angle, rotor axial position, and blade tip clearance.…”
Section: Numerical Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, the augmentation of velocity for diffusers is significantly influenced by the length of the diffuser and its opening angle [31][32][33][34]. Moreover, adding a flange to the diffuser is thought to further improve velocity augmentation [11,[35][36][37]. While the cylindrical section primarily serves as a housing for the turbine, its throat length is crucial as it can influence airflow, thereby affecting velocity augmentation.…”
Section: Introductionmentioning
confidence: 99%